Contributions to the discipline of positive organizational scholarship - Cameron, Kim S.; Arran Caza (2004)
Positive organizational scholarship is the study of that which is positive, flourishing, and life-giving in organizations. Positive refers to the elevating processes and outcomes in organizations. Organizational refers to the interpersonal and structural dynamics activated in and through organizations, specifically taking into account the context in which positive phenomena occur. Scholarship refers to the scientific, theoretically derived, and rigorous investigation of that which is positive in organizational settings. This article introduces this new field of study and identifies some of its key contributions. - Reproduced.
Keywords: Organizations